Kebijakan Satu Peta dan Satu Data dalam Program Percepatan Pengadaan Informasi Geospasial Dasar dan Informasi Geospasial Tematik (Kerja Sama Badan Informasi Geospasial Dengan Badan Usaha Milik Negara) - Ulfiah, Ulfiah; Amran Koto, Eryus; Ningsih, Sari (FIA Unkris Press, 2024)
One of the important things that is often overlooked in the development process is the utilization of geospatial information as one of the most important data in supporting planning, implementation, monitoring and evaluation. If this is not considered carefully, it will certainly cause damage to the environment and less than optimal All of them are interrelated, connected, influence and influenced, so a single geospatial information is needed that can be used as a reference. Government policy through Presidential Regulation No. 23 of 2021 concerning the Acceleration of One Map Policy Implementation, provides a mandate to increase the Map Accuracy Level from Scale 1:50,000 to Scale 1:5,000